A TPD-based determination of the graphite interlayer cohesion energy - Weippert, Juergen; Hauns, Jakob; Bachmann, Julian; Boettcher, Artur; Yao, Xuelin; Yang, Bo; Narita, Akimitsu; Muellen, Klaus; Kappes, Manfred M. (Journal of Chemical Physics, 2018)
Temperature Programmed Desorption (TPD) spectroscopy was used to determine the binding energies of polycyclic aromatic hydrocarbons CnHm (22 ≤ n ≤ 60) with highly oriented pyrolytic graphite. These energies were then used to estimate the dispersive graphite interlayer cohesion by means of a refined extrapolation method proposed by Björk et al. This yields a cohesion energy of 44.0 ± 3.8 meV per carbon atom. We discuss some limits of the TPD-based approach and contrast our values with previous determinations of the interlayer cohesion energy of graphite.
CRIS-Team Scopus Importer:2022-04-14